2017
DOI: 10.1302/2046-3758.612.bjr-2017-0112.r1
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in tendon disease

Abstract: ObjectivesEmerging evidence indicates that tendon disease is an active process with inflammation that is critical to disease onset and progression. However, the key cytokines responsible for driving and sustaining inflammation have not been identified.MethodsWe performed a systematic review of the literature using MEDLINE (U.S. National Library of Medicine, Bethesda, Maryland) in March 2017. Studies reporting the expression of interleukins (ILs), tumour necrosis factor alpha (TNF-α) and interferon gamma in dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
73
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 73 publications
1
73
0
2
Order By: Relevance
“…Cytokines, such as interleukins, TNF-α, and interferon gamma are known to be key players in tendon disorders. They are released by the tendon stroma or immunoregulatory cells in response to mechanical stress or tissue injury, alter the cellular phenotype, and induce changes in matrix production [62]. Our in vitro data demonstrated the absence of endogenous expression of IL-1β and TNF-α in both groups.…”
Section: Discussionmentioning
confidence: 54%
“…Cytokines, such as interleukins, TNF-α, and interferon gamma are known to be key players in tendon disorders. They are released by the tendon stroma or immunoregulatory cells in response to mechanical stress or tissue injury, alter the cellular phenotype, and induce changes in matrix production [62]. Our in vitro data demonstrated the absence of endogenous expression of IL-1β and TNF-α in both groups.…”
Section: Discussionmentioning
confidence: 54%
“…Besides, there is an increase of the ratio type III/type I collagen (Birch et al, ; Ireland et al, ; Xu and Murrell, ). Previous studies reported also that there is a decrease of collagen type I at protein level (John et al, ; Schulze‐Tanzil et al, ; Morita et al, ), mainly, because TNF‐ α induces the activation of MMPs and a subsequent degradation of collagen type I (Magra and Maffulli, ; Fang et al, ; Tsai et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Despite TNF‐α group had a high expression of collagen type I, all the treated group exhibited lower expression showing values closer to that found in tenocytes not subjected to inflammation. The cellular response to treatment with TNF‐α in tendon cells showed an increase of collagen type I (Morita et al, ). In tendinopathy cases, it is noted that there is an increase of expression of type I collagen as well as the percentage of denatured collagen.…”
Section: Discussionmentioning
confidence: 99%
“… 40 A systematic review on cytokines in tendon disease showed that the expressions of IL-1β, IL-6 and TNF-α in animal tendon injury models tend to increase from the early phase of tendon healing, whereas IL-6 was the only cytokine involved in human tendon disease and found to be elevated in tendon tears. 41 Further investigation is needed into the role of these cytokines in the development of tendon disease. In this study, the higher expression of IL-6 in tenocytes in vitro and Achilles tendon from diabetic rats was seen under high glucose conditions.…”
Section: Discussionmentioning
confidence: 99%